Frequency of Raised Bedside Index for Severity in Acute Pancreatitis (BISAP) and Ranson Score in Patients of Acute Pancreatitis: BISAP and Ranson Score in Patients of Acute Pancreatitis - Riaz, Usman; Javed, Salman; Aslam, Umbreen; Yousaf, Hassaan; Nawaz, Muhammad Haseeb; Mohibullah, .; Waseem, Humaira (Pakistan Journal of Health Sciences, 2025)
Acute pancreatitis is a growing abdominal disorder that presents a major surgical problem to general surgeons across the globe. Objectives: To identify the raised Bedside Index for Severity in Acute Pancreatitis (BISAP) and Ranson scores frequencies in patients with acute pancreatitis. Methods: The cross-sectional descriptive study was carried out on 120 patients in the Emergency Department of the Sheikh Zayed Hospital in Lahore. Patients who fit into the inclusion criteria were enrolled. Clinical histories, physical examinations, and laboratory investigations were conducted in detail. Each patient had their BISAP and Ranson scores calculated- BISAP on initial presentation and Ranson scores at admission and 48 hours. There were high levels of BISAP and Ranson scores that were stipulated based on the operational standards. The data analysis was done in SPSS version 23.0. Results: The average age of the participants was 44.92 ± 8.92 years; 46 (38.3%) were male and 74 (61.7%) female. It was seen that a high BISAP and Ranson scores occurred in 28 (23.3%) and 42 (35%) patients, respectively. The percentage of patients who had an increased BISAP was 23.3, and the percentage of patients who had an increased Ranson score was 35, which means that a higher percentage were classified as severe by the Ranson classification criteria. Conclusions: The BISAP score is a convenient, valid, and time-saving instrument to evaluate the severity of acute pancreatitis at an early stage and risk classification in clinical practice, although the Ranson might be more effective in this regard.